Building Brand Community - McAlexander,Jim; Schouten ,John; Koenig,Hal (Journal of Marketing, 2002)
Drawing from ethnographic and quantitative work with owners of Jeep and Harley-Davidson vehicles, the authors examine the phenomenon of brand community as a potential basis for sustainable competitive advantage. The authors develop an expanded conceptualization of brand community and test its usefulness in both theory and practice. A brand community from a customer-experiential perspective is a fabric of relationships in which the customer is centrally situated. Crucial components of the brand community are customers' relationships with the brand, with the firm, with the product in use, and with fellow customers. The relationships that form a brand community develop in contexts that are dynamic and subject to marketing influence. Variables such as geographic concentration, richness of social context, duration of contact, and memberships in multiple or overlapping communities all mediate the experience of community. In this article, the authors examine the influence of brandfeststhat is, programs strategically designed to enhance customer experience with the brandon the many component relationships of a brand community. The results demonstrate that marketers can strengthen brand communities by facilitating shared customer experiences. Finally, this work yields a new and richer conceptualization of customer loyalty as integration in a brand community. According to the analysis, a customer's loyalty to a brand consists of the cumulative and holistic effect of all the relationships the customer experiences as a member of a brand community.
Keywords: Marketing